Balanced Chromosomal Rearrangement Detection by Low‐Pass Whole‐Genome Sequencing. (24th January 2018) - Dong, Zirui; Ye, Lingfei; Yang, Zhenjun; Chen, Haixiao; Yuan, Jianying; Wang, Huilin; Guo, Xiaosen; Li, Yun; Wang, Jun; Chen, Fang; Cheung, Sau Wai; Morton, Cynthia C.; et al.
Abstract: Balanced chromosomal rearrangements (or balanced chromosome abnormalities, BCAs) are common chromosomal structural variants. Emerging studies have demonstrated the feasibility of using whole‐genome sequencing (WGS) for detection of BCA‐associated breakpoints, but the requirement for a priori knowledge of the rearranged regions from G‐banded chromosome analysis limits its application. The protocols described here are based on low‐pass WGS for detecting BCA events independent from chromosome analysis, and has been validated using genomic data from the 1000 Genomes Project. This approach adopts non‐size‐selected mate‐pair library (3∼8 kb) with 2∼3 μg DNA as input, and requires only 30 million read‐pairs (50 bp, equivalent to 1‐fold base‐coverage) for each sample. The complete procedure takes 13 days and the total cost is estimated to be less than $600 (USD) per sample. © 2018 by John Wiley & Sons, Inc.